Multiband metamaterial-inspired antenna using split ring resonator. (June 2020) - Thamil Selvi, N.; Thiruvalar Selvan, P.; Babu, S.P.K.; Pandeeswari, R.
Abstract: A novel compact Coplanar Wave Guide (CPW)-fed metamaterial (MTM)-inspired multiband antenna is designed for Wireless Local Area Network (WLAN), C-Band, Universal Mobile Telecommunication System (UMTS) and Worldwide Interoperability for Microwave Access (WiMAX) applications. The new multiband antenna with the dimensions of 40 × 40 × 0.8 mm 3 is fabricated on FR4 substrate. It consists of circular shaped Split Ring Resonator (SRR) with five rings and resonates at 2.10 GHz (UMTS), 2.9 GHz (WLAN), 3.5 GHz (WiMAX), 4.5 GHz (C-band), 5.7 GHz (WLAN) and 6.5 GHz (WLAN-IEEE 802.11ax). Parametric studies are performed on a number of metallic rings, height of the CPW-fed ground plane and different substrate materials for the proposed penta-ring SRR. A prototype antenna is fabricated and the results are measured to examine the simulated results. The measurement of the radiation pattern shows an omnidirectional pattern in H-plane and a dipole like pattern in E-plane.